Heteroditopic receptors for ion-pair recognition. - McConnell, A; Beer, P (2012)
Ion-pair recognition is a new field of research emerging from cation and anion coordination chemistry. Specific types of heteroditopic receptor designs for ion pairs and the complexity of ion-pair binding are discussed to illustrate key concepts such as cooperativity. The importance of this area of research is reflected by the wide variety of potential applications of ion-pair receptors, including applications as membrane transport and salt solubilization agents and sensors.